Food safety and energetics analysis of the heat treatment of milk - Korzenszky Péter; Kovács Ágnes; Meixner Richárd; Pettkó Csaba (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2017)
The food safety and energy efficiency of the heat treatment of cow’s milk was investigated by our research group. Of the known heat treatment processes, the results of our investigation are presented in the case of a cow’s milk treated at 75 °C and held for 5 minutes. Proper treatment of cow’s milk is probably the most pivotal issue in food production, but from the point of view of the manufacturing plant, food safety and the amount of energy used for the production are important as well. Our measurements were carried out using the PG 015 pasteurizer of the Department of Food Hygiene of the University of Veterinary Medicine. The electricity input and the amount of heat used during the technology were measured. The efficiency of food production was defined as the ratio of the utilized energy to the energy invested. To verify the adequacy of the heat treatment, peroxidase enzyme inactivity tests were performed untreated milk, and for treated milk, without and with holding it at the given temperature for the proper length of time. Based on our measurement results it can be stated that a heat recovery zone built into the technology keeps the COP (coefficient of performance) value above one. By optimizing the length of the heating and the heat treatment, by adjusting the desired technological temperature precisely, and by the application of food safety limit values and analyses, the efficiency of a larger system can be improved significantly as well.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék